ANALYSIS OF GROSS PROFIT IN IMPROVING THE EFFICIENCY OF THE TUNAS HARAPAN BAUMATA KUPANG BUSINESS GROUP: indonesia - Zainudin Adang Djaha (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2024)
The formulation of the problem in this research is how to obtain profits in terms of changes in sales volume, selling price and cost price obtained by the Tunas Harapan Baumata Kupang Business Group in increasing business efficiency. The objectives to be achieved in this research are knowing the amount of gross profit based on changes in sales volume, knowing the amount of gross profit based on changes in selling price, knowing the amount of gross profit based on changes in cost price and knowing the amount of gross profit based on changes in sales volume, selling price and cost price. The type of data used in this research is quantitative data with the data source being secondary data. Data collection techniques use document study. The data analysis technique used is as follows: a). Gross Profit Analysis using Volume Difference with the following formula: Sales Volume Difference = SVDU x LKPUd. Information SVDU = Volume Difference in Units; LKPUd = Budgeted Gross Profit Per Unit, b) Gross Profit Analysis using the price difference with the following formula: Selling Price Difference = SHJP x VPTr. Note: SHJP = Sales Price Difference, VPTr = Realized Sales Volume, c). Gross Profit Analysis using the difference in Cost Price with the following formula: Difference in Cost Price = SHPPu x VPTr; Note: SHPPu = Difference in Cost of Goods Per Unit, VPTr = Volume VPTr = Realized Sales Volume. The research results show that the difference in sales volume made by business groups provides a profit of Rp. 940,000, the amount of profit obtained exceeds the planned profit of IDR 16,530,000. This means that the difference in profit due to an increase in the selling price is IDR 16,590,000. The difference between the budgeted cost per unit and the actual cost per unit is IDR. 25, Because the budgeted cost per unit is smaller than the actual cost per unit, the difference in cost is called loss difference. Thus, the amount of loss that occurs due to changes in the cost price per unit is IDR. 11,060,000, the difference in profitable volume is IDR. 940,000, the difference in selling price also results in a profit of Rp. 16,590,000, while the difference in cost price experienced a loss of Rp. 5,530,000. The cost price experienced a loss due to the actual cost price not being in accordance with the budgeted cost price